IMPLEMENTASI KONSEP DASAR KEBIJAKAN PENIDDIKAN ISLAM DI INDONESIA - yuike silvira (Al Ulya: Jurnal Pendidikan Islam, 2021)
Education is one of the determining factors for the progress of a nation in the future. And to realize an education into quality education, a policy is needed to regulate the process of running an education. And by implementing a good policy in education, it will be able to help education in Indonesia to solve various problems that exist, especially problems that exist in education itself. This study aims to analyze the implementation of the basic concepts of Islamic education policy in Indonesia and to find out about the meaning of Islamic education policy, the functions and principles of policy, types and problems of policy, the process of analyzing educational policies, and strategies for implementing education policies. The method used in this research is to use the library research method, in which the researcher examines journals, books, notes, and others, as well as examines the results of existing studies, as well as other data collected. relevant. The results of this study are 1) Implementation of Islamic education policies, 2) Functions and principles of educational policy analysis, 3) Types and Problems of Education Policies, 4) Education Policy Analysis Process, 5) Education Policy Implementation Strategies.